Effect of beet pulp pellets fed steers wintering and finishing rations - Arehart, L.A.; Banbury, Evans E. (Kansas State University. Agricultural Experiment Station, 2011)
Sugar beet by-products are available to cattle feeders in northwestern Kansas, but their value as livestock feed is not known. In 1967-68, steers fed liquid protein concentrate beet pulp pellets (LPC) in wintering rations gained faster (1.96 vs. 1.24 lb. per day) than steers on similar amounts of alfalfa hay. Then on finishing rations, gain per day favored alfalfa-fed cattle (2.58 to 2.25 lb. per day). In 1968-69, there was no significant difference between beet pellets and alfalfa, but 5.0 lb. LPC beet pellets reduced feed consumption and daily gains compared with results from rations involving alfalfa (wintering 1.33 to 1.19 lb. per day; finishing 2.5 to 2.14 lb. per day). Last year, Colby Experiment Station evaluated dried molasses-beet pulp pellets in wintering and finishing rations.
Keywords: Beef; Beet pulp; Steers; Wintering rations; Finishing rations